Application of PCR for the detection of bovine tuberculosis in cattle (Journal of the Bangladesh Agricultural University, 2011)
The present study was carried out for the detection and identification of bovine tuberculosis (bTB) using polymerase chain reaction (PCR). A total of 10 suspected cattle of Savar and BAU dairy farm were examined. Lymphnode biopsy, nasal swabs and blood were collected. Smears from lymphnode biopsy and nasal swabs were made onto clear slides and stain with acid fast staining. Portion of lymohnodes were preserved at -200C and extracted DNA for PCR analysis. Portion of lymphnodes and other tissues were also collected in 10% neutral buffered formalin for routine Hematoxilin and Eosin staining and acid fast staining. In this study, acid fast staining of lymphnodes and nasal smears failed to detect acid fast Mycobacterium. The genome of bovine Mycobacterium in the extracted DNA of lymphnodes which used in PCR reaction was amplified and yielded 600 bp amplicon. This study suggests that, the PCR technique is a useful and rapid diagnostic tool for the identification of bovine TB in dairy cattle. Amplification technology offers the potential for the diagnosis of TB in a few hours with a high degree of sensitivity and specificity. Keywords: Bovine TB; acid fast; PCR DOI: http://dx.doi.org/10.3329/jbau.v9i1.8747 JBAU 2011; 9(1): 73-78